Modeling and simulation of complex dynamic musculoskeletal architectures - Xiaotian Zhang (Nature Portfolio, 2019)
Natural creatures, from fish to snake and birds, combine neural control, sensory feedback and compliant mechanics to operate across uncertain environments. Here the authors present a versatile modeling approach to the dynamic simulation of their architectures based on the assembly of Cosserat rods.